Antioxidant and C5a-blocking strategy for hepatic ischemia–reperfusion injury repair - Zhang, Xiaobing (J Nanobiotechnology, 2021)
BACKGROUND: Nonspecific liver uptake of nanomaterials after intravenous injection has hindered nanomedicine for clinical translation. However, nanomaterials’ propensity for liver distribution might enable their use in hepatic ischemia–reperfusion injury (IRI) repair. During hepatic IRI, reactive oxygen species (ROS) are generated and the fifth component of complement (C5a) is activated. In addition, C5a is confirmed to exacerbate the vicious cycle of oxidative stress and inflammatory damage. For these reasons, we have investigated the development of nanomaterials with liver uptake to scavenge ROS and block C5a for hepatic IRI repair. RESULTS: To achieve this goal, a traditional nanoantioxidant of nanoceria was surface conjugated with the anti-C5a aptamers (Ceria@Apt) to scavenge the ROS and reduce C5a-mediated inflammation. High uptake of Ceria@Apt in the liver was confirmed by preclinical positron emission tomography (PET) imaging. The clinical symptoms of hepatic IRI were effectively alleviated by Ceria@Apt with ROS scavenging and C5a blocking in mice model. The released pro-inflammatory cytokines were significantly reduced, and subsequent inflammatory reaction involved in the liver was inhibited. CONCLUSIONS: The synthesized Ceria@Apt has great potential of medical application in hepatic IRI repair, which could also be applied for other ischemic-related diseases. GRAPHIC ABSTRACT: [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12951-021-00858-9.